2016
DOI: 10.1371/journal.pone.0149286
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Olfactory Bulb Volume in Parkinson’s Disease: A Systematic Review and Meta-Analysis

Abstract: ObjectiveThe changes in olfactory bulb (OB) volume in Parkinson’s disease (PD) patients have not yet been comprehensively evaluated. The purpose of this meta-analysis was to explore whether the OB volume was significantly different between PD patients and healthy controls.MethodsPubMed and Embase were searched up to March 6, 2015 with no language restrictions. Two independent reviewers screened eligible studies and extracted data on study characteristics and OB volume. Additionally, a systematic review and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 34 publications
3
36
0
Order By: Relevance
“…In the meta-analysis and review (Li et al, 2016 ), it was reported that PD patients presented a significantly larger OB volume on the right hemisphere, indicating the presence of lateralized differences between the two hemispheres. In support, several articles have indicated that the right hemisphere is more important for higher-order processing of smell sensation that the left hemisphere (Zatorre et al, 1992 ; Jones-Gotman and Zatorre, 1993 ; Hummel et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the meta-analysis and review (Li et al, 2016 ), it was reported that PD patients presented a significantly larger OB volume on the right hemisphere, indicating the presence of lateralized differences between the two hemispheres. In support, several articles have indicated that the right hemisphere is more important for higher-order processing of smell sensation that the left hemisphere (Zatorre et al, 1992 ; Jones-Gotman and Zatorre, 1993 ; Hummel et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…Impairments in PD are associated with the presence of lewy bodies, which represent distinctive inclusion bodies that underlie neuroanatomical dysfunctions in this condition. Lewy bodies are present from the earliest stage of PD, identified in the olfactory nucleus and the OB, but also in the dorsal nucleus of the vagus nerve (DMV) (Li et al, 2016 ). The spread of lewy bodies throughout the stages of PD, initially begins at the DMV, then spreads throughout the brainstem nuclei to the substantia nigra-pars compacta and finally the cortex (Braak et al, 2003 ; Doty, 2012 ; Li et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vice versa, the coinhibitory factor PD-1 negatively regulates CD8 +cell function by facilitating oxidative metabolism 48. The connection between PD and cancer has been raised but poorly characterised 49. Taken together, our GO and KEGG analysis of differentially expressed genes distinguished CD8 +T cell exhaustion associated with HCC from CHB and provided pivotal clues for future investigation.…”
Section: Discussionmentioning
confidence: 85%
“…Specifically, patients with hypos-PD showed reduced activation in the bilateral rectus, orbitofrontal cortex (OFC), amygdala and parahippocampus and reduced functional connectivities between the left rectus and prefrontal, temporal, occipital, and limbic areas, compared with healthy controls (HCs) 14 . Structural MRI studies using region-of-interest (ROI) methods have unraveled the neuroanatomical basis of the metabolic and functional changes and have found that olfactory-related atrophy occurred not only in the primary olfactory cortex (e.g., the piriform and amygdala), but also extended to the OFC, temporal, parietal-occipital, and cingulate cortex in PD 9 , 15 17 .…”
Section: Introductionmentioning
confidence: 99%